Time of Day When Type 1 Diabetes Patients With Eating Disorder Symptoms Most Commonly Restrict Insulin. Issue 2 (February 2018) - Merwin, Rhonda M.; Moskovich, Ashley A.; Honeycutt, Lisa K.; Lane, James D.; Feinglos, Mark; Surwit, Richard S.; Zucker, Nancy L.; Dmitrieva, Natalia O.; Babyak, Michael A.; Batchelder, Heather; Mooney, Jan
ABSTRACT: Objective: Restricting insulin to lose weight is a significant problem in the clinical management of type 1 diabetes (T1D). Little is known about this behavior or how to effectively intervene. Identifying when insulin restriction occurs could allow clinicians to target typical high-risk times or formulate hypotheses regarding factors that influence this behavior. The current study investigated the frequency of insulin restriction by time of day. Methods: Fifty-nine adults with T1D and eating disorder symptoms completed 72 hours of real-time reporting of eating and insulin dosing with continuous glucose monitoring. We used a generalized estimating equation model to test the global hypothesis that frequency of insulin restriction (defined as not taking enough insulin to cover food consumed) varied by time of day, and examined frequency of insulin restriction by hour. We also examined whether patterns of insulin restriction for 72 hours corresponded with patients' interview reports of insulin restriction for the past 28 days. Results: Frequency of insulin restriction varied as a function of time ( p = .016). Insulin restriction was the least likely in the morning hours (6:00–8:59 AM), averaging 6% of the meals/snacks consumed. Insulin restriction was more common in the late afternoon (3:00–5:59 PM), peaking at 29%. Insulin was restricted for 32% of the meals/snacks eaten overnight (excluding for hypoglycemia); however, overnight eating was rare. Insulin restriction was associated with higher 120-minute postprandial blood glucose (difference = 44.4 mg/dL, 95% confidence interval = 22.7–68.5, p < .001) and overall poorer metabolic control ( r = 0.43–0.62, p 's < .01). Patients reported restricting insulin for a greater percentage of meals and snacks for the past 28 days than during the 72 hour real-time assessment; however, the reports were correlated (Spearman's ρ = 0.46, p < .001) and accounted for similar variance in HbA1c (34% versus 35%, respectively). Conclusions: Findings suggest that insulin restriction may be less likely in the morning, and that late afternoon is a potentially important time for additional therapeutic support. Results also suggest that systematic clinical assessment and treatment of overnight eating might improve T1D management.